Early pulmonary disease in systemic sclerosis: a comparison between carbon monoxide transfer factor and static lung compliance. Issue 10 (October 1993) - Scheja, A; Akesson, A; Wollmer, P; Wollheim, F A
Abstract : OBJECTIVES--Pulmonary disease is responsible for considerable morbidity and mortality in systemic sclerosis (SSc). Static lung compliance (Cst) has been observed to be decreased more often in SSc than the vital capacity, indicating that it is a sensitive measure of lung restriction. In this study Cst was compared with the carbon monoxide transfer factor (TLCO), a widely used measure of the function of the alveolar capillary unit, and with lung volumes in 59 patients with confirmed or suspected SSc. METHODS--Cst was calculated from the oesophageal pressure at different lung volumes and the TLCO was measured with the single breath method. RESULTS--The TLCO was found to be the earliest sign of pulmonary disease and was already decreased at a disease duration of one year or less. Surprisingly, no relation was found between the TLCO and smoking habits, nor the degree of peripheral vascular disease. The TLCO correlated with the Cst and vital capacity. CONCLUSIONS--An early pulmonary lesion can be identified in patients with SSc with decreased TLCO at a time when no fibrotic changes are manifested.